Aplicación de la contabilidad gerencial para la empresa de muebles “San Eduardo” ubicada en la parroquia Mulaló, cantón Latacunga, provincia de Cotopaxi - Gutiérrez Toscano, Marco Antonio (2022)
The entitled current work main Management Accounting Application in the “San Eduardo” Furniture Enterprise, located in the Mulaló parish from Latacunga canton had the aims of explaining Management Accounting and its application into PYMES from various perspectives and approaches; to make an accounting area situational analysis and use the Cost-Volume-Profit Model as an administrative tool. The used methodology was supported a quantitative approach. This research was descriptive, exploratory and documentary type based on the different reliable bibliographic sources research. The achieved results with the Cost-Volume-Utility Model application in the enterprise: show a $82.01 total cost for the executive desk with a $17.99 profit, at the same time, the cabinet cost amounted to $111.22 with a $28.78 profit. The quarterly break-even point for desks was 8 units and for cabinets 10. These data allow the enterprise to make timely management decisions.